Minimum wages in the 21st century - Arindrajit Dube; Attila Lindner (Rockwool Foundation Berlin (RF Berlin) and Centre for Research & Analysis of Migration (CReAM), 2024)
This chapter surveys the literature on the impact of minimum wages on low-wage labor markets. We describe and critically review the empirical methods in the new minimum wage literature, particularly those leveraging quasi-experimental variation. We provide a quantitative overview of the most recent evidence on the employment and wage effects of the policy, while also exploring emerging research on its impact on other margins, including amenities, other inputs (such as capital and high-skilled workers), firm entry and exit, output prices and demand, profits, and productivity. This approach allows us to present a comprehensive picture of how minimum wage policies affect firms, workers, and labor markets. We also review the evidence on the policy's impact on wage inequality and income distribution. Finally, we discuss how these effects can vary depending on the economic context and the level of a country's development.
Keywords: 330; minimum wages; labor demand; employment and wage effects; margins of adjustment; inequality